Gender discriminatory taxes, fairness perception, and labor supply - Jochen Hundsdoerfer; Eva Kristina Matthaei (Freie Universität Berlin, School of Business & Economics, 2020)
In this paper, we examine the gender specific impact of discriminatory taxation on fairness perception and individual labor supply decisions. Using the controlled environment of an experimental laboratory, we manipulate both distributional as well as procedural justice of taxation between subjects. We violate distributional fairness through the random application of tax rates, while procedural justice is broken by levying discriminatory tax rates based on taxpayer gender. For both inequality in outcome as well as discrimination, we find strong differences in reactions between male and female participants. Male participants perceived gender discriminatory taxation as unfair in and of itself. Female participants perceived random taxation as well as gender discriminatory taxation to be unfair, as long as they ended up with the higher tax rate. The perceived fairness strongly drove (did not affect) male (female) participants' labor supply. Taken both subgroups together, while mere outcome inequality did not influence labor supply decisions significantly, we find evidence of a negative effect of gender-based discrimination on labor supply.
urn:nbn:de:kobv:188-refubium-27045-0
Keywords: 330; Tax; labor supply; distributional justice; procedural justice; discrimination